Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fncel.2015.00153
|View full text |Cite
|
Sign up to set email alerts
|

Stim and Orai proteins in neuronal Ca2+ signaling and excitability

Abstract: Stim1 and Orai1 are ubiquitous proteins that have long been known to mediate Ca2+ release-activated Ca2+ (CRAC) current (ICRAC) and store-operated Ca2+ entry (SOCE) only in non-excitable cells. SOCE is activated following the depletion of the endogenous Ca2+ stores, which are mainly located within the endoplasmic reticulum (ER), to replete the intracellular Ca2+ reservoir and engage specific Ca2+-dependent processes, such as proliferation, migration, cytoskeletal remodeling, and gene expression. Their paralogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 112 publications
7
115
0
Order By: Relevance
“…The reticular distribution of s-1R-YFP was recapitulated using a s-1R-mCh construct that was cotransfected with a green fluorescent protein-tagged STIM1. STIM1 is a sensor of Ca 21 levels in the ER and forms part of the store operated calcium entry response after Ca 21 depletion from the ER (Kraft, 2015;Moccia et al, 2015). As expected, STIM1-YFP overlapped extensively with s-1R-mCherry (s-1R-mCh; Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The reticular distribution of s-1R-YFP was recapitulated using a s-1R-mCh construct that was cotransfected with a green fluorescent protein-tagged STIM1. STIM1 is a sensor of Ca 21 levels in the ER and forms part of the store operated calcium entry response after Ca 21 depletion from the ER (Kraft, 2015;Moccia et al, 2015). As expected, STIM1-YFP overlapped extensively with s-1R-mCherry (s-1R-mCh; Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Both stromal interaction molecule (STIM) and ORAi proteins, key players in SOCE, and ryanodine receptors, ER-localized Ca 2+ channels responsible for Ca 2+ -induced Ca 2+ release at the ER-PM junction in muscle (75,77), are expressed in neurons (78,79). Similarly, isoforms of junctophilin, another integral protein of the ER membrane that binds the PM in trans and functions as an accessory factor of the ryanodine receptors at muscle triads, are expressed in neurons (80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies evaluated the optimal conditions for the differentiation of MSCs to tenocytes, chondrocytes, or bone cells The results showed that mesenchymatous cell differentiation toward a tendon or bone phenotype depended on the degree of tensile loading: higher tensile loads promoted osteogenic differentiation (38). Mechanosensitive calcium permeable channels, such as the TRP channel, generate changes in intracellular calcium concentration in response to various mechanical stimuli (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Activation of these channels at the level of plasma membrane of MSCs would induce intracellular calcium release and confirm the hypothesis that the mechanical tension could also activate MSCs in the pathological process that leads to the development of the SpAs (55-57).…”
Section: Immunoregulationmentioning
confidence: 99%